The Long-run Effects of Teacher Collective Bargaining - Michael Lovenheim; Alexander Willén (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper presents the first analysis of the effect of teacher collective bargaining on long-run labor market and educational attainment outcomes. Our analysis exploits the different timing across states in the passage of duty-to-bargain laws in a difference-in-difference framework to identify how exposure to teacher collective bargaining affects the long-run outcomes of students. Using American Community Survey (ACS) data linked to each respondent's state of birth, we examine labor market outcomes and educational attainment for 35-49 year olds. Our estimates suggest that teacher collective bargaining worsens the future labor market outcomes of students: living in a state that has a duty-to-bargain law for all 12 grade-school years reduces earnings by 800 (or 2%) per year and decreases hours worked by 0.50 hours per week. The earnings estimate indicates that teacher collective bargaining reduces earnings by 199.6 billion in the US annually. We also find evidence of lower employment rates, which is driven by lower labor force participation, as well as reductions in the skill levels of the occupations into which workers sort. The effects are driven by men and nonwhites, who experience larger relative declines in long-run outcomes. Using data from the 1979 National Longitudinal Survey of Youth, we demonstrate that collective bargaining leads to sizable reductions in measured cognitive and non-cognitive skills among young adults. Taken together, our results suggest laws that support collective bargaining for teachers have adverse long-term labor market consequences for students.
Keywords: I20; J45; J58; 330; teachers unions; teacher labor markets; economics of education; collective bargaining